CULTURAL DIFFERENCES BETWEEN INDIA AND EUROPE, THE CHANCE FOR AN INTERNATIONALLY OPERATING MANAGEMENT - Manfred, Lach (European Scientific Journal, ESJ, 2014)
The indian market ist growing very fast and therefore most important for many companies who are willing to export to low-cost countries. But the idea to sell goods in India requires more than just installing a distribution and production organization. Personal experience from the Autor of this Article has shown that adapting the products tested in Europe to local conditions has not lead to the desired success so far. The new approach is to develop new products with lower performance at very low costs by understanding the local costumers requirements. The following article gives an Idea about the circumstances of doing business in India and wants to give an overview about criteria which needs to be taken into consideration to gain success in the indian markets and how to transfer know how from home markets to foreign sites.